LITERASI KEWIRAUSAHAAN UNTUK MENCIPTAKAN WIRAUSAHA MUDA DI ERA EKONOMI DIGITAL - Avelius Dominggus Sore; Yopinus Bobi; Yulia Suryanti; Dessy Triana Relita; Yunita Astikawati (STKIP Persada Khatulistiwa Sintang, 2026)
ABSTRACTThe development of the digital economy provides significant opportunities for young people to develop technology-based businesses. However, the level of digital entrepreneurial literacy among vocational high school students is still relatively low, requiring systematic educational and training initiatives. This community service program aims to improve students' entrepreneurial literacy and encourage the emergence of young entrepreneurs in the digital economy era among students of SMK Nusantara Indah in Sintang Regency. The program implementation was carried out through several stages, including needs identification, digital entrepreneurship socialization, entrepreneurship literacy training, and mentoring in developing digital-based business ideas. A total of 40 students participated in this activity. To evaluate the impact of the program, surveys were conducted before and after the training activities. The initial survey results indicated that students' understanding of digital entrepreneurship was relatively low, with 45% of students categorized as having low understanding, 35% moderate understanding, and only 20% high understanding. After the program implementation, there was a significant improvement, where 65% of students reached a high level of understanding, 25% moderate, and only 10% remained in the low category. Furthermore, the evaluation results also showed a high level of participant satisfaction with the training activities provided. These findings indicate that the digital entrepreneurship literacy program effectively improved students' knowledge, motivation, and confidence in developing technology-based business ideas. Therefore, strengthening entrepreneurship literacy programs in vocational education institutions should continue to be developed to foster young entrepreneurs who are creative and adaptive to the evolving digital economy.Keywords: entrepreneurship literacy, digital economy, young entrepreneurs, vocational education ABSTRAKPerkembangan ekonomi digital memberikan peluang besar bagi generasi muda untuk mengembangkan usaha berbasis teknologi. Namun demikian, tingkat literasi kewirausahaan digital di kalangan siswa sekolah menengah kejuruan masih relatif rendah sehingga diperlukan upaya edukasi dan pelatihan yang sistematis. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan literasi kewirausahaan siswa serta mendorong terbentuknya wirausaha muda di era ekonomi digital pada siswa SMK Nusantara Indah Kabupaten Sintang. Metode pelaksanaan kegiatan dilakukan melalui beberapa tahapan, yaitu identifikasi kebutuhan mitra, sosialisasi kewirausahaan digital, pelatihan literasi kewirausahaan, serta pendampingan dalam pengembangan ide usaha berbasis digital. Sebanyak 40 siswa terlibat sebagai peserta dalam kegiatan ini. Untuk mengetahui dampak program, dilakukan survei sebelum dan setelah kegiatan pelatihan. Hasil survei awal menunjukkan bahwa tingkat pemahaman siswa terhadap kewirausahaan digital masih tergolong rendah, dengan 45% siswa berada pada kategori pemahaman rendah, 35% kategori sedang, dan 20% kategori tinggi. Setelah pelaksanaan program, terjadi peningkatan yang signifikan di mana 65% siswa berada pada kategori pemahaman tinggi, 25% kategori sedang, dan hanya 10% kategori rendah. Selain itu, hasil evaluasi juga menunjukkan tingkat kepuasan peserta yang tinggi terhadap kegiatan pelatihan yang diberikan. Hasil kegiatan ini menunjukkan bahwa program literasi kewirausahaan digital mampu meningkatkan pemahaman, motivasi, serta kepercayaan diri siswa dalam mengembangkan ide usaha berbasis teknologi. Oleh karena itu, program penguatan literasi kewirausahaan di lingkungan pendidikan vokasi perlu terus dikembangkan untuk mendorong terciptanya generasi wirausaha muda yang kreatif dan adaptif terhadap perkembangan ekonomi digital.Kata Kunci: literasi kewirausahaan, ekonomi digital, wirausaha muda, pendidikan vokasi